(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
We present the first cycle of a Design Based Research in Atsiame, Ghana. Starting with a hypothetical learning trajectory, intervention sessions are carried out while performing daily improvement microcycles where results are analyzed and, if needed, redesigned. Using Fuson’s frame of reference, we lean on Bruner’s CPA and guided discovery to study how children learn to count. When the intervention was finalized (abruptly because of the worldwide COVID-19 pandemic), students showed a better understanding of numbers’ construction, counting and tens, as well as an improvement in their number-modelling strategies.